A survey of the needs and demands of the library users of the Mindanao State University implication to library service - Manta, Warlinda V. (1995)
This survey was conducted to find out the demands and needs of faculty and graduate and undergraduate student users of the Mindanao State University (MSU) Library and their satisfaction with MSU Library resources.